Analisis Kebutuhan Sarana dan Prasarana Pendidikan di SMP Negeri 11 Palembang (Indo-MathEdu Intellectuals Journal, 2024)
This research discusses the analysis of the need for facilities and infrastructure at SMP Negeri 11 Palembang. This study is a qualitative research with a descriptive approach. Data collection methods include interviews, observations, and documentation. The data analysis techniques involve data collection, data presentation, verification, and drawing conclusions. To ensure the validity of the data, the researcher used triangulation. It can be concluded that the needs analysis of facilities and infrastructure at the school has been well implemented. The purpose of this analysis is to identify the facilities and infrastructure needed by the school community. The analysis process begins with compiling a list of needs through coordination meetings between the principal, the vice principal in charge of facilities and infrastructure, teachers, staff, and administrative employees. The second step is cost estimation by estimating the required costs. The third step is setting priorities based on the results of the coordination meeting, considering the urgency or level of importance. The final step is to prepare a procurement plan, which includes a report on the results of the school's needs analysis, classification of needs, and the preparation of a proposal submitted to the City Education Office. If approved, the proposal will be reviewed and assessed for feasibility to obtain approval from the relevant parties